SUPERVISI AKADEMIK KEPALA SEKOLAH DALAM MEMOTIVASI KINERJA GURU AGAMA HINDU DI SMP NEGERI 1 TEMBUKU BANGLI - I Putu Eka Pradnyana; I Nyoman Temon Astawa; Marsono (JAPAM (Jurnal Pendidikan Agama), 2025)
Hindu religion teacher are axpacted to perform at their best in their teaching practices, inorder to produce students with good spiritual quality and character. However, entering the 5.0 erabrings many dynamics in the education space tha pose challenges to the learning process of Hindureligion by Hindu teacher, including demanding the extence of school principals to contribute to theperformance of Hindu religion teachers. This also occurs at SMP Negeri 1 Tembuku as one of theeducational institutions in Bangli Regency, Bali. The data in this study is sourced from primary andsecondary data, which is collected by observation techniques, interviews, documentation studies andliterature. The collected data was then analyzed with leadership theory, integrative constructiontheory and achievement motivation theory. The results of the study are then described descriptively.The results of this study are as follows: first, the academic supervision of the school principal inmotivating the performance of Hindu religion teachers at SMP Negeri 1 Tembuku Bangli begins withplanning and realizing performance targets. Second, the strengthening of the academic supervisionprocess of the principal of SMP Negeri 1 Tembuku Bangli is achieved through collaborationregardless of professional background or work culture, intense communication with internal andexternal parties of the school, and establishing contexts to facilitate the development targets of Hindureligion teachers. The third implications of academic supervision are the development of Hinducognition, emotional stability, and real actions to achieve optimal performance. The analysis isbeneficial to inspire the movement of supervision and the advancement of Hindu religious teachers'performance in all junior high school units. It can be concluded that through academic supervision,the principal of SMP Negeri 1 Tembuku is able to provide motivation both morally and through theacademic administration system towards improving the quality of Hindu religious teachers'performance.